KURANGNYA DUKUNGAN SUAMI DAN DUKUNGAN TENAGA KESEHATAN PADA IBU HAMIL TRIMESTER III TERHADAP AKTIVITAS HUBUNGAN SEKSUAL DI KOTA MAGELANG - Siti Chunaeni; Bagoes Widjanarko; Zahroh Shaluhiyah (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2014)
Background: Pregnancy that happened to women will cause the changes in physic, emotion and also sexual intention in each trimester. That sexual intention is effected by interact, emotion and physic factors. Sometimes, some husbands also have scare during sexual intercourse due to premature delivery. If the husband can control their feel to make sexual intercourse, they consider to keep their wife’s pregnancy. The pregnancy can disturb their sexual intercourse, one of them is any physical and emotional changes in each semester include sexual intents changes.Aims: to know the effect of supporting from husband and medical staffs for pregnant women trimester III to sexual activity in Magelang City. It used analytic survey with cross sectional approach. The populations were 102 pregnant mothers with ≥32 weeks in trimester III. Collecting data technique used analytic questioner data with bivariate statistic test chi square and multivariate with logistic regressive.Result: most respondents are 18,6 % active and 81,4 % un active. Factors that relate to sexual activity are husband’s support with statistical test p value < 0,05. Multivariate analysis results show that influential factors with OR / Exp (B) = 6,045 score, it means that the pregnant mother trimester III who gets husband’s support will be active in doing sexual intercourse 6,045 times than the mother who doesn’t get husband’s support.For medical staffs are hoped to increase the counseling to pregnant mother about sexual intercourse in pregnancy with her couples’ participation.